DEVELOPMENT OF INTERACTIVE VIDEO BASED ON LOOMIE LIVE APPLICATION ASSISTED BY NEARPOD AS LEARNING MEDIA ON THE SUBJECT OF CHEMICAL BONDS - Haetami, Aceng; Karsita, Elma; Maysara, Maysara; Dahlan, Dahlan; Esnawi, Esnawi; Arsyad, Muhammad (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The abstract nature of chemical bonding concepts often results in low student engagement and suboptimal learning outcomes, particularly when instruction relies on teacher-centered approaches. This study aimed to develop and evaluate an interactive video learning medium based on the Loomie Live application integrated with Nearpod and structured using the Problem-Based Learning (PBL) model. Employing a Research and Development (R&D) design, the study involved expert validation, small-group trials (n = 9), and field implementation with 30 tenth-grade students. Data were collected using validation sheets, practicality questionnaires, observation sheets, and pretest–posttest instruments, and analyzed using percentage criteria and N-gain scores. The results indicated that the developed media achieved high validity (media aspect = 80.55%; material aspect = 78.27%), very high practicality (teacher response = 92.43%; student response = 95.83%), and strong effectiveness (N-gain = 0.8, high category). Student learning activity reached 84.28%, indicating very active engagement. The novelty of this study lies in the integration of real-time animated video production (Loomie Live) with interactive assessment features (Nearpod) within a PBL framework, enabling synchronous conceptual visualization and formative feedback in chemistry learning. The findings imply that technology-enhanced, problem-based interactive video can significantly improve conceptual understanding and learner engagement in abstract science topics. This model offers a scalable digital learning innovation adaptable to secondary chemistry education contexts.